2022
DOI: 10.3390/joitmc8040194
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socio-Cultural Factors on Knowledge-Based Innovation and the Digital Economy

Abstract: The knowledge economy, fostered by knowledge-based innovation, has been linked to entrepreneurial and economic success, especially in OECD countries. Studies have shown the influence of socio-cultural factors on almost every area of economic behavior. However, few studies have attempted to connect these factors to the knowledge economy. Our research bridges this gap. We investigated the impact of socio-cultural factors on knowledge-based innovation, then we also examined whether digitalization impacted knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Also, for expenses on ICT, we postulate, based on the results of prior studies, that regions with higher ICT expenses perform better in the digital economy [63]. This study followed the recommendations for using the Pearson correlation coefficient by Benesty et al [64] and the recent practices of Vlasov et al [12] on a similar research area. The analysis can be statistically explained as follows:…”
Section: Marital Status Number Of Divorces Per 1000 Marriagesmentioning
confidence: 93%
See 2 more Smart Citations
“…Also, for expenses on ICT, we postulate, based on the results of prior studies, that regions with higher ICT expenses perform better in the digital economy [63]. This study followed the recommendations for using the Pearson correlation coefficient by Benesty et al [64] and the recent practices of Vlasov et al [12] on a similar research area. The analysis can be statistically explained as follows:…”
Section: Marital Status Number Of Divorces Per 1000 Marriagesmentioning
confidence: 93%
“…Furthermore, research has demonstrated that social and cultural factors can influence the use of digital technologies in societies, particularly among ethnic minority groups [11,12]. A survey of the Scopus citation database of studies between 2015 and 2017 shows a sharp increase in publications on the digital economy (from 509 to 3585) and socio-cultural factors (from 540 to 1030).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the innovation process, society’s faith and customs cannot be overlooked (Shyan Fam et al , 2004). Hence, Vlasov et al (2022) examined the effect of sociocultural determinants on knowledge-based innovation in the context of OECD countries. The empirical data supported the hypothesis that religious beliefs and other aspects of social culture had a sizable impact on the development of new forms of knowledge.…”
Section: Review Of Literaturementioning
confidence: 99%
“…As examples of such development: backbone innovation-active clusters, on the basis of which a technopolis is formed. Technopolis is a special form of spatial organisation of productive forces, aimed at creating a base for the rapid development of knowledge-intensive industries, which should subsequently give an impetus to the progressive growth of the economy of certain regions and the economy of the country as a whole [10].…”
Section: Introductionmentioning
confidence: 99%